Cannabinoid interventions for improving cachexia outcomes in cancer: a systematic review and meta‐analysis. Issue 1 (8th December 2021) - Simon, Lucile; Baldwin, Christine; Kalea, Anastasia Z.; Slee, Adrian
Abstract: Cancer‐associated cachexia (CAC) is a wasting syndrome characterized by involuntary weight loss and anorexia. Clear definition and diagnostic criteria for CAC are lacking, which makes it difficult to estimate its prevalence, to interpret research and to compare studies. There is no standard treatment to manage CAC, but previous studies support the use of cannabinoids for cachexia in other chronic diseases including HIV and multiple sclerosis. However, only a few randomized controlled trials (RCTs) and one meta‐analysis of this intervention in cancer populations are available. Non‐randomized studies of interventions (NRSIs) are often excluded from reviews due to variable methodology and potential for biases. This review aimed to consider NRSIs alongside RCTs to provide a complete summary of the available evidence that clinical decision makers could use in future investigations. Literature searches were conducted using three databases for relevant RCTs or NRSIs according to Cochrane methodology. Abstract and full texts of retrieved manuscripts were selected and retrieved by two investigators based on the PRISMA‐A guidelines, and risk of bias and quality of evidence assessments were performed. Outcome data on weight, appetite, quality of life, performance status, adverse effects, and mortality were combined by narrative synthesis and meta‐analysis where possible. Ten studies were included, four of which were RCTs and six NRSIs matching the eligibility criteria. Very low‐quality evidence from meta‐analysis suggested no significant benefits of cannabinoids for appetite compared with control (standardized mean difference: −0.02; 95% confidence interval: −0.51, 0.46; P = 0.93). Patient‐reported observations from NRSIs suggested improvements in appetite. Another meta‐analysis of moderate quality evidence showed that cannabinoids were significantly less efficient than active or inactive control on quality of life (standardized mean difference: −0.25; 95% confidence interval: −0.43, −0.07; P = 0.007). The effectiveness of cannabinoids alone to improve outcomes of CAC remains unclear. Low‐quality evidence from both RCTs and NRSIs shows no significant benefits of cannabinoids for weight gain, appetite stimulation, and better quality of life, three important outcomes of cachexia. Higher quality research integrating cannabinoids into multi‐modal therapies may offer better opportunities for developing CAC‐specific treatments. This review also highlights that findings from non‐randomized studies of interventions (NRSIs) can provide evidence of the effects of an intervention and advocate for the feasibility of larger RCTs.